Retinal Ganglion Cells and Circadian Rhythms in Alzheimer’s Disease, Parkinson’s Disease, and Beyond - La Morgia, Chiara; Ross-Cisneros, Fred N.; Sadun, Alfredo A.; Carelli, Valerio (Frontiers in Neurology, 2017)
There is increasing awareness on the role played by circadian rhythm abnormalities in neurodegenerative disorders such as Alzheimer’s and Parkinson’s disease. The characterization of the circadian dysfunction parallels the mounting evidence that the hallmarks of neurodegeneration also affect the retina and frequently lead to loss of retinal ganglion cells and to different degrees of optic neuropathy. In the retinal ganglion cell population there is the subgroup of cells intrinsically photosensitive and expressing the photopigment melanopsin (mRGCs), which are now well known to drive the entrainment of circadian rhythms to the light-dark cycles. Thus, the correlation between the pathological changes affecting the retina and mRGCs with the circadian imbalance in these neurodegenerative diseases is now clearly emerging, pointing to the possibility that these patients might be amenable to and benefit from light therapy. Currently, this connection is better established for Alzheimer’s and Parkinson’s disease, but the same scenario may apply to other neurodegenerative disorders, such as Huntington’s disease. This review highlights similarities and differences in the retinal/circadian rhythm axis in these neurodegenerative diseases posing a working frame for future studies.